Employees' entrepreneurial contributions to firms in Russia, 1995-2004 - Richard Croucher; Marian Rizov (Human Resource Management Journal, 2011)
This article examines how employee self-reported entrepreneurial contributions evolved in firms operating in Russia in 1995-2004 and whether changes can be explained by Akerlof's theory of implicit gift exchange in labour contracts. We find that these contributions were indeed influenced by wage premia and shifting work norms, declining by about a half during the period and with a particularly marked fall in contributions by manual workers. The trend was found among foreign-owned, private Russianowned and state-owned companies. Akerlof's model therefore helps explain Russian workers' changing behaviour.
Keywords: D22; J21; J24; J31; 330; employee entrepreneurship; implicit gift exchange; labour contracts; transition